Perbedaan Waktu Pemulihan Motorik Ekstremitas Inferior pada Laki-laki dan Perempuan yang Dilakukan Subarachnoid-Block (SAB) - Ubah Swasono Basuki; Pandit Sarosa; Maryana (Jurnal Keperawatan Notokusumo, 2014)
Background: individual leg muscle strength measured by the degree of movement against the barrier.Bromage score is one indicator of motor response after spinal anesthesia. Objective: This study aimed to know the difference between inferior extremity motor recovery in men and women who performed subarachnoid block (SAB) in IBS Dharma HusadaHospital Probolinggo. Method: This study is an observational analytic study, using quantitative methods to obtain a picture of the difference between the inferior extremity motor recovery in men and women who do Subarachnoid - Block (SAB). Result: Based on the findings in Dharma HusadaHospital Probolinggo, December 2013 to January 2014 the number of 60 respondents patient men and women, carried subarachnoid block (SAB), at the age of 17-45, medicine bupivakain0,5% 15mg spinal anesthesia,that men are inferior extremity motor recovery time of 14.5 minutes faster than women, men motor recovery time 152.5 minutes while the women's 166 minutes. Conclusion: The inferior extremity motor recovery time in males average 152.5 minutes, while women 166 minutes. So DAPT concluded extremity motor recovery time inferior to men 14.5 minutes faster than women